The Efficacy and Safety of Ureteric Stent Removal with Strings versus No Strings: Which Is Better?. (15th October 2020) - Luo, Zhenkai; Jiao, Binbin; Zhao, Hang; Huang, Tao; Geng, Lin; Zhang, Guan
Abstract : Objective . To evaluate the current evidence on the effectiveness and safety of ureteric stent removal using strings compared to conventional methods. Materials and Methods . The electronic databases PubMed, Embase, China National Knowledge Infrastructure (CNKI), and the Cochrane Library were systematically searched up to March 2020. Two reviewers searched the literature, independently extracted the data, and evaluated the quality of the studies according to the inclusion and exclusion criteria. The data analysis was performed with the software program Review Manager 5.3. Results . Eleven studies with a total of 1809 patients were included in the analysis based on the inclusion criteria. Our meta-analysis showed that visual analogue scale (VAS) scores were significantly lower in the string group than in the conventional group (weighted mean difference (WMD) -2.63; 95% confidence interval (CI) -3.68, -1.58; P < 0.00001 ). In terms of stent dwell time, the string group had an advantage (WMD -9.53; 95% CI -14.20, -4.86; P < 0.0001 ). In addition, no significant differences in the occurrence of urinary tract infection (UTI) (odds ratio (OR) 1.03; 95% CI 0.62, 1.72; P = 0.92 ), emergency room visits (OR 0.99; 95% CI 0.59, 1.67; P = 0.97 ), or other complications (P > 0.05 ) were observed between the two groups. Conclusion . Our findings suggest that an extraction string is an effective and safe method for the removal of ureteric stents. This method gives patients the benefits of reduced pain and shortened stent dwell time without increasing the risk of UTI. Nevertheless, these findings should be further confirmed through large-volume, well-designed prospective randomized controlled trials (RCTs).